Integrating or Not-Integrating—That is the Question. Effects of Integrated Instruction on the Development of Pre-Service Biology Teachers’ Professional Knowledge - Kramer, Maria; Förtsch, Christian; Neuhaus, Birgit J. (Frontiers in Education, 2021)
For successful classroom instruction, teachers require a well-founded knowledge base consisting of the three knowledge facets pedagogical-psychological knowledge (PK), content knowledge (CK), and pedagogical content knowledge (PCK). However, there is not yet clarity about the circumstances and instructional pathways through which teachers can best develop these knowledge facets. In an experimental study (N = 118 pre-service biology teachers), we investigated the effects of separated instruction (knowledge facets were treated successively without linking) or integrated instruction (knowledge facets were presented in an interrelated way) on PK, CK, PCK and the application of PCK in a video-based assessment tool in comparison to a control group (receiving no instruction). Both pathways of instruction were provided by a lecturer on the curricular topic of senses and sensory organs, exemplified for the topic skin. Results point to the effectiveness of both ways of instruction in terms of knowledge increases for CK and PCK. In addition, working with the video-based assessment tool may have had an additional effect on PCK. No effects for PK could be found, possibly due to a ceiling effect. Moreover, there was no effect of the intervention on the application of PCK. However, tendencies in descriptive results indicating a possible advantage concerning separated or integrated instruction with regard to CK and PCK are discussed. Overall, our results indicate that the use of video-based tools can complement instructional approaches to knowledge acquisition.